Light Weight Low Cost X-Band Antennas and Waveguide Components Using Electroplated 3D Printed Plastics - Wirth, Sebastian; Morrow, Ivor L.; Andre, Daniel; Finnis, Mark V. (Cranfield University, 2017)
Poster presented at the 2017 Defence and Security Doctoral Symposium.Low weight and low cost are attractive features in many antenna and waveguide applications including mobile communication, remote sensing and medical scenarios. Electroplating shaped three-dimensional printed plastic components to produce highly conductive surfaces is one advantageous approach. This research contributes to the newly developed design procedure, manufacture and measurements of a 3D printed microwave pyramidal horn antenna electoplated with a 40 um copper coating and a novel flat 3D printed Graded Refractive Index (GRIN) lens. The antenna, waveguide and lens are printed in two pieces, the lens is then attached to the horn antenna aperture to provide a highly collimated radiated beam. Measurements conducted at Cranfield University Antennas and Ground Based SAR (AGBSAR) laboratory on the antenna matching radiated fields and gain demonstrate the performance meets, and in some cases exceeds, that of a standard X-band milled aluminium horn antenna and waveguide but with significantly reduced weight and cost. When the lens is attached to the horn antenna aperture an increase in antenna radiated gain of 5dBi over a 200 MHz bandwidth at 10 GHz is demonstrated. The hybrid antenna-lens sensor is highly suitable for near-field ground penetrating radar imaging of buried landmines. We acknowledge the financial support of the Sir Bobby Charlton Charity "Find A Better Way".
Keywords: 'Horn antenna'; 'Ground-penetrating-radar'; '3D-printing'; 'DSDS17'; 'DSDS17 poster'; 'Photogrammetry and Remote Sensing'; 'Antennas and Propagation'